The potential of recycling wool residues as an amendment for enhancing the physical and hydraulic properties of a sandy loam soil - Ahmed Abdallah; Francesca Ugolini; Silvia Baronti; Anita Maienza; Francesca Camilli; Laura Bonora; Francesca Martelli; Jacopo Primicerio; Fabrizio Ungaro (International Journal of Recycling of Organic Waste in Agriculture)
Purpose Climate change and global food demand in coming decades urge effective actions for more efficient uses of water and soil resources. This paper reports the preliminary findings of a study assessing the potential of sheep scoured wool residues (SWRs) as soil amendments to enhance the physical and hydraulic properties of a sandy loam soil under rain conditions. Method Two different SWRs were used: scoured residues (white wool, WW) and carbonized scoured residues (black wool, BW) at different SWRs/soil ratios (0.0, 0.5, 1.0 and 2.0%). Soil bulk density (BD), total porosity (TP), aggregates stability, aggregate size distribution, saturated hydraulic conductivity, and water retention properties were determined under rain conditions, in addition to rainwater balance (storage, percolation and runoff). Results Both WW and BW, particularly at the high wool/soil ratio (2%), significantly reduced soil BD by 11.98% and 9.85%, respectively. Moreover, WW and BW increased TP by 16.45% and 13.57% and available water capacity by 6.5% and 18.1%, respectively. SWRs increased the formation of macro-aggregates and increased aggregate stability. The results of rainwater balance showed higher percolation percentages and less rainwater storage in the wool-treated soil. Conclusion The increase in water percolation is in line with the increased total porosity and the higher saturated hydraulic conductivity of wool-treated soil. Despite the high capacity of absorbing water, SWRs affected the water movement of the soil more than its water retention.